KEANEKARAGAMAN MAKROZOOBENTHOS SEBAGAI BIOINDIKATOR PENCEMARAN AIR SUNGAI SUNGGAL DI DESA SRIGUNTING PROVINSI SUMATERA UTARA - Danra Siallagan; Yunasfi Djayus; Zulham Apandy Harahap (Program Studi Manajemen Sumberdaya Perairan, Fakultas Pertanian Universitas Sumatera Utara, 2014)
The research have been done on May – June 2014 in the Village Sunggal Srigunting North Sumatera. This study aims to determine the status of water quality in accordance with the standard Government Regulation No. 82 of 2001 and analyze the diversity macrozoobenthos. Sampels were collected from three stations by Purposive Random Sampling method. Physical and chemical parameters were analyzed using Storet method while biological parameters using Shannon-Wienner equation.The results of this research show that the water quality status of River Village is experiencing light pollution to the station I (agricultural waste) and pollution being experienced for the second station (sewage and industrial bath taps) and station III (domestic waste). The level of diversity found in the River makrozoobenthos Sunggal Srigunting Village North Sumatra province belongs to the moderate level of diversity with diversity values ranged from 1.35 to 2.24. Value diversity is highest at the third station of 2.24 and the value of diversity was lowest for the first station at 1.35, while the value of diversity in station II is equal to 1.83.Key Words: Diversity, Macrozoobenthos, Sunggal River